Diagnostic Examination of Infectious Bursal Disease on Broiler Chicken Farming In Majalengka. West Java - Amany, Nafisa Raihana; Majid, Rully Abiyoga; Qomariyuti, Refina; Fajrin, Rizni; Hartady, Tyagita; Viqih, Muhammad (Jurnal Veteriner; Vol 25 No 1 (2024)DO - 10.19087/jveteriner.2024.25.1.113, 2024)
Broiler chicken is a type of chicken that grow fast. The presence of a disease cause the diminished of body weight. A case study was found on broiler chicken farms in Majalengka with a high mortality and clinical symptoms appeared of lethargy, tremor, diarrhea, white, bloody and green feces, fever, standing hair, and paleness. Supporting examinations were carried out include necropsy, PCR, and ELISA. The results of pathological findings were hemorrhage of bursa of Fabricius, thigh and chest muscle. There were also found nephrosis, hydropericardium, and enteritis. PCR resulted positive for Infectious Bursal Disease (IBD) Virus and the mean of antibody titer was 2,767 of ELISA. Based on anamnesis, indications, cage and environmental observations, clinical symptoms, physical examination, and supporting diagnostics, the broilers from the farms in Majalengka were affected by IBD. IBD is a disease caused by the RNA virus of the Birnaviridae family which has a mortality of 56.09% in broilers. The main predisposing factor found in the farm was the excess of chlorine in the drinking water. Treatments were given to maintain and increase the body’s immunity of the chickens to reduce the secondary infection was the Hexamine and vitamins. The administration of chlorine in the drinking water were stopped. The treatments were successful proved the decrease of the depletion rate after the incubation period.